2010
DOI: 10.3390/ma4010104
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Coaxial Waveguides with Complex Shapes of Cross-Sections

Abstract: In this paper, we describe waveguide properties of new optical waveguides made of noble metals and filled with glass and air. Such waveguides are coaxial cables and differ from a conventional coaxial in the shape of their central rods. Coaxial waveguide with annular and elliptic central rods are considered. Numerical simulations demonstrate that these waveguides, having nanosize cross-section, support propagation of few comparatively low-loss modes, having phase velocity close to the speed of light and the fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…where z eff o k n k    , with eff n the imaginary part of the effective refractive index of each mode [30]. Our results are shown in Fig.…”
Section: Resultsmentioning
confidence: 73%
“…where z eff o k n k    , with eff n the imaginary part of the effective refractive index of each mode [30]. Our results are shown in Fig.…”
Section: Resultsmentioning
confidence: 73%
“…81 It was found that the waveguides with elliptical cross section inner electrodes produced faster group velocity than those with circular cross sections, when a dipole-like field is propagated. On the other hand, the TEM mode did not change notably with a change in shape of the inner electrode cross section.…”
Section: ) Applicationsmentioning
confidence: 99%
“…Kozina, et al investigated theoretically the propagation of electromagnetic elds in coaxial waveguides with different geometries of the inner core, those being circular and elliptical cross sections. 81 It was found that the waveguides with elliptical cross section inner electrodes produced faster group velocity than those with circular cross sections, when a dipole-like eld is propagated. On the other hand, the TEM mode did not change notably with a change in shape of the inner electrode cross section.…”
Section: (1) Introductionmentioning
confidence: 99%
“…Plasmonics is the discipline describing the bridging between electromagnetic radiation and electronic oscillations. Recently, the research activity related to plasmonics has undergone a strong acceleration owing to the important role that it can play in different and important fields, such as nanomedicine [ 1 , 2 , 3 , 4 , 5 ], biosensing [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ] nanophotonics [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], photovoltaic applications [ 29 , 30 , 31 , 32 ] or catalysis [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%